Fibrosing Frontal Alopecia: A comprehensive study to understand its etiology (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze the latest data on the etiology, mechanisms, clinical signs, diagnostic methods and therapeutic approaches for Fibrosing Frontal Alopecia (FFA). Methods: Systematic review organized around five phrases: formulation of the guiding question and the acronym PICO, search for articles and studies in online databases, selection and review of studies, critical evaluation of the material in the selected articles and interpretation of the results. Bibliographic Review: Fibrosing frontal alopecia is a form of acquired primary cicatricial alopecia characterized clinically by a recession of the frontotemporal line, often accompanied by eyebrow alopecia. Its pathophysiology involves immunological, genetic, hormonal, photoexposure, cosmetic use, environmental factors, trauma and stress mechanisms. The diagnosis is made clinically, through physical examinations and trichoscopy, and can be complemented with biopsy and optical coherence tomography. Conclusion: As this is a relatively new pathology, more research is still needed to better understand the disease and establish more effective treatments.